Improve Netizens’ Perception of The Image of Anhui-Based on The Research of Zhihu-Related Anhui Review - Jin, Ying; He, Min; Li, Yazheng (Advances in Social Sciences Research Journal, 2023)
Since the 18th National Congress of the Communist Party of China, the Party Central Committee, with Comrade Xi Jinping as its core, has attached great importance to Anhui development and has visited the six provinces of Shanxi, Henan, Anhui, Hubei, Hunan, and Jiangxi in the central region. The central region has accelerated the rise of the rise. At the two conferences of the country in 2022, General Secretary Xi Jinping proposed the "five musts," emphasizing the important position of image construction in urban development. The construction of the urban image is an important part of developing economic and cultural undertakings and the prosperity of socialist culture. The image of the city is a portrayal of multiple appearances and rich connotations in a city. It is the product of subjective blending. Whether it is a local person who feels about the city or the foreign people who know through the TV network, the mass media will affect their right impression of the city. In the new era of communication, the audience has a new opportunity to define the image of the city.